Analisis Pengaruh Brand Trust Terhadap Brand Loyalty pada Aplikasi E-Wallet DANA - Djami, Fredy; Maulany, Raymond (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This research aims to analyze the influence of brand trust on brand loyalty in the DANA e-wallet application. Along with advances in computer and telecommunications technology, fintech such as DANA has made financial transactions easier for the public. Brand trust, as customer trust in a brand, is believed to increase brand loyalty, namely customer loyalty to a brand. This research was conducted using a quantitative approach and involved 100 DANA e-wallet application users in Kancah Village, RT 04, RW 15 Cihideung Village, Prongpong District as respondents. The research instrument is a questionnaire that measures the level of brand trust and brand loyalty based on predetermined indicators. The data analysis method uses simple linear regression and correlation analysis to determine the relationship between brand trust and brand loyalty. This research shows that the results of regression analysis show that Brand Trust has a positive and significant influence on Brand Loyalty. This means that the higher the level of consumer trust in a brand, the higher their level of loyalty to that brand. The Brand Trust variable plays an important role in predicting Brand Loyalty in this research. Overall, this research concludes that Brand Trust is an important factor that influences the level of Brand Loyalty among DANA e-wallet application users, and the higher the level of consumer trust in a brand, the higher the level of loyalty to that brand.